The attitude of Latin American immigrants in Florida (USA) towards deceased organ donation – a cross section cohort study - Ríos, Antonio; López‐Navas, Ana Isabel; García, José Antonio; Garrido, Gregorio; Ayala‐García, Marco Antonio; Sebastián, María José; Hernandez, Antonio Miguel; Ramírez, Pablo; Parrilla, Pascual (Transplant international, 2017)
Summary The Latin American (LA) population resident in the USA is a growing subgroup of the population. To find out the structure of attitude towards organ donation in the LA population resident in Florida (USA). A sample was taken of LA residents in Florida, randomized and stratified by nationality, age and sex (n = 1524). Attitude was assessed using a validated questionnaire (PCID–DTO Rios) that was self‐completed anonymously. The survey completion rate was 95% (n = 1450). Attitude was favourable in 33% of respondents (n = 485), against in 40% (n = 575) and undecided in 27% (n = 390). The following variables were associated with a favourable attitude: country of origin (Dominican Republic; P = 0.038); sex (female; P < 0.001); marital status (married; P < 0.001); level of education (university; P < 0.001); previous experience of the subject (P < 0.001); considering the need for a transplant in the future (P < 0.001); understanding the concept of brain death (P = 0.003); attitude towards donating a family member's organs (P < 0.001); having discussed organ donation and transplantation with one's family (P < 0.001) or with one's partner (P < 0.001); participation in pro‐social type activities (P < 0.001); the respondent's religion (atheist–agnostic; P < 0.001); a respondent's knowledge of the attitude of his or her religion towards organ donation (P < 0.001); no concern about mutilation after donation (P < 0.001); acceptance of cremation (P < 0.001); burial (P < 0.001); and an autopsy if one were needed (P < 0.001). The attitude towards donation of LA in Florida is worse than that reported in the native population and is associated with certain psychosocial factors.